Indigoidine – Biosynthesized organic semiconductor. (December 2019) - Yumusak, Cigdem; Prochazkova, Anna Jancik; Apaydin, Dogukan Hazar; Seelajaroen, Hathaichanok; Sariciftci, Niyazi Serdar; Weiter, Martin; Krajcovic, Jozef; Qin, Yong; Zhang, Wei; Zhan, Jixun; Kovalenko, Alexander
Abstract: Indigoidine is a blue natural pigment, which can be efficiently synthetized in E. coli . In addition to its antioxidant and antimicrobial activities indigoidine due to its stability and deep blue color can find an application as an industrial, environmentally friendly dye. Moreover, similarly to its counterpart regular indigo dye, due to its molecular structure, indigoidine is an organic semiconductor. Fully conjugated aromatic moiety and intermolecular hydrogen bonding of indigoidine result in an unusually narrow bandgap for such a small molecule. This, in its turn, result is tight molecular packing in the solid state and opens a path for a wide range of application in organic and bio-electronics, such as electrochemical and field effect transistors, organic solar cells, light and bio-sensors etc. Highlights: Indigoidine a natural pigment synthetized in E. coli . Fully conjugated aromatic moiety results in a narrow bandgap of 1.3 eV in thin films. Indigoidine has unusually low LUMO of −4.3 eV. In OFETs indigoidine shows ambipolar behavior.